Evaluasi Kinerja Karyawan PT. XYZ dengan Pendekatan Metode Fuzzy Mamdani - Muharni Muharni; Widiarti Awaliah; Dewi Fatmawati Surianto (Sakura Digital Nusantara, 2025)
Employee performance evaluation is vital for organizational effectiveness, ensuring fair and objective assessments. PT. XYZ, a cement distributor, struggles with subjective evaluation criteria, prompting the need for a more accurate approach. This study applies the Fuzzy Mamdani method to improve performance assessment. Data from 31 employees were collected through literature reviews, interviews, and observations. The system uses salary, age, and years of service as input variables, while the output variable represents employee performance. The Fuzzy Mamdani method processes data through fuzzification, fuzzy inference, and defuzzification to handle uncertainty and enhance evaluation fairness. The results show that 29 employees fall under the